Effects of Traffic Density on Measured Sound Levels – A Case Study - Matthew, Ian; Amarra, Anthony (Canadian Acoustics, 2016)
In road noise prediction algorithms/models, it is commonly accepted that the sound emission from a road segment (the cumulative sound output from a stream of moving vehicles) increases at a rate of 3 decibels for each doubling in the number of vehicles passing the measurement point within a given period of time. In essence, this corresponds to a doubling of the emitted sound energy for a doubling in the vehicle count. This relationship is intuitively correct and has been proven accurate for various road noise models in use today. This results in a daily sound emission pattern which typically peaks during the busiest hours of the day (morning and afternoon “rush” hours) and is lower during those hours for which traffic is reduced. However, consider the resultant daily sound emission pattern when the vehicular density commonly exceeds the critical density for a given roadway. By way of case study, this paper examines a 72-hour measurement window at receptor points adjacent to the Don Valley Parkway in the City of Toronto – a roadway which commonly exceeds the critical vehicular density. The study examines the true daily sound emission pattern for this specific traffic scenario.